Social Compatibility and It is Relationship to Self-Confidence (An Applied Study on A Sample of Students at King Abdulaziz University in Jeddah Province) - Almabadi, Mohammed Ahmed (Journal of Humanities & Social Sciences, 2024)
This study aimed to identify social compatibility and its relationship to self-confidence and the university's role in enhancing it among university students, through the use of social survey as a method of study to collect data through the questionnaire tool from a random sample of students from the Faculty of Arts and Humanities at King Abdulaziz University in Jeddah amounted to (401) students from different departments. The study reached many important results such as: that the availability of social compatibility among the study sample was significant, and most of the factors that showed this reality were the ability to agree with the university's environment, while it appeared that the least of these factors is the fear of the sample members from facing social situations whatever type it is; and it became clear that the lack of selfishness among the university student and self-love more than others is the most contributing factor in enhancing self-confidence among the sample members, while the least factors are that the academic achievement encourages university students to more learning, as it turned out that the university has a role about the extent of the availability of these factors, which came in a large measure .The most important factor in establishing the university's various sports activities and competitions, and they have no selfishness and love themselves more than others, while the least aspect was that the university's evaluation of community dialogues for students. The study also found that there is no statistically significant effect of the variable of university specialization on the axes of study, while there are statistically significant differences in the variables of the academic level, participation in extra-curricular activities, and the level of father’s education in the axis of “aspects that gain the student's self-confidence”, and there are also statistically significant differences between the GPA, the level of mother’s education, and the level of family income in the university’s role in social compatibility.
Keywords: self-confidence; social adjustment; university student